Risk of breast cancer in relation to the interval since last full term pregnancy. - Cummings, P. (BMJ Group, 1994)
OBJECTIVE--To examine whether the risk of breast cancer is increased by a recent term pregnancy. DESIGN--Population based case-control study. SETTING--Eight areas in the United States. SUBJECTS--Cases were 2279 multiparous women residents of the eight areas aged 25-49 who were diagnosed as having breast cancer during 1980-2. Controls were 2357 multiparous women selected from the same areas by random digit dialing. MAIN OUTCOME MEASURE--Relative risk of developing breast cancer according to the time interval since last full term pregnancy. RESULTS--The distribution of intervals since the last term pregnancy was similar in cases and controls. Adjusted for age, parity, and age at first term pregnancy, the odds ratios observed for categories of years since the last full term pregnancy were: 0-2 years, odds ratio 1.16 (95% confidence interval 0.84 to 1.59); 3-6 years, odds ratio 1.21 (0.95 to 1.54); 7-9 years, odds ratio 1.04 (0.84 to 1.38); > or = 10 years, odds ratio 1.00 (reference). CONCLUSIONS--Among multiparous women aged 25-49 years there was no association between the risk of breast cancer and the time interval since the last full term pregnancy.